Risk Mitigation of Corporate Social Performance in US Class Action Lawsuits. Issue 2 (3rd April 2021) - Fauser, Daniel V.; Utz, Sebastian
Abstract : We investigated the relationship between corporate environmental, social, and governance (ESG) performance and litigation risk by examining US class action lawsuits. We found that a 1 standard deviation improvement in the ESG controversies of an average company in the sample reduced litigation risk from 3.1% to 2.4%. Moreover, an average company with low ESG performance exhibited a loss in market value twice as large as that of a company with high ESG performance—an abnormal loss of US1.14 billion. Implementation of our findings with a trading strategy yielded positive monthly alphas, suggesting that investors benefit from lower litigation risk and the insurance-like protection of high ESG performance. Abstract : Disclosure: The authors report no conflicts of interest. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Editor's note: Submitted 24 April 2020 Accepted 1 December 2020 by Stephen J. Brown. This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Jie Cao and one anonymous reviewer were the reviewers for this article.